DNA metabarcode analyses reveal similarities and differences in plant microbiomes of industrial hemp and medicinal Cannabis in China - Li, Jiayang; Zhang, Hong; Long, Songhua; Li, Wenting; Wang, Tuhong; Yu, Jian; Zhou, Ying; Zou, Shuo; Zhu, Hongjian; Xu, Jianping; Cheng, Yi (Frontiers in Microbiology, 2025)
Endophytic bacteria within plant tissues play crucial roles in plant health, stress tolerance, and contribute to the metabolite diversity of host plants. Cannabis sativa L. is an economically significant plant, with industrial hemp (IH) and medicinal Cannabis (MC) being the two main cultivars. However, the composition and functional traits of their endophytic bacterial communities in roots and leaves are not well understood. In this study, DNA metabarcode sequencing were employed to compare the bacterial communities between IH and MC. Significant differences were observed in the root and leaf niches. IH roots were enriched with stress-tolerant bacteria, while MC roots showed higher levels of biofilm-forming bacteria. In leaves, differences were even more pronounced, particularly in the abundance of Gram-negative bacteria, potential pathogens, stress-tolerant bacteria, and biofilm-forming bacteria. PICRUSt2 functional predictions revealed differences in nitrogen metabolism and secondary metabolite biosynthesis pathways in different cultivars and niches, while FAPROTAX analysis highlighted variations in carbon, nitrogen, and sulfur cycling functions. These findings underscore the distinct roles of bacterial communities in regulating plant health, stress responses, and metabolic processes in different niches and cultivars, providing insights for improving cultivation practices and plant resilience.